LDLR-Gene therapy for familial hypercholesterolaemia: problems, progress, and perspectives - Al-Allaf, Faisal A (BioMed Central, 2010)
Coronary artery diseases (CAD) inflict a heavy economical and social burden on most populations and contribute significantly to their morbidity and mortality rates. Low-density lipoprotein receptor (LDLR) associated familial hypercholesterolemia (FH) is the most frequent Mendelian disorder and is a major risk factor for the development of CAD. To date there is no cure for FH. The primary goal of clinical management is to control hypercholesterolaemia in order to decrease the risk of atherosclerosis and to prevent CAD. Permanent phenotypic correction with single administration of a gene therapeutic vector is a goal still needing to be achieved. The first ex vivo clinical trial of gene therapy in FH was conducted nearly 18 years ago. Patients who had inherited LDLR gene mutations were subjected to an aggressive surgical intervention involving partial hepatectomy to obtain the patient's own hepatocytes for ex vivo gene transfer with a replication deficient LDLR-retroviral vector. After successful re-infusion of transduced cells through a catheter placed in the inferior mesenteric vein at the time of liver resection, only low-level expression of the transferred LDLR gene was observed in the five patients enrolled in the trial. In contrast, full reversal of hypercholesterolaemia was later demonstrated in in vivo preclinical studies using LDLR-adenovirus mediated gene transfer. However, the high efficiency of cell division independent gene transfer by adenovirus vectors is limited by their short-term persistence due to episomal maintenance and the cytotoxicity of these highly immunogenic viruses. Novel long-term persisting vectors derived from adeno-associated viruses and lentiviruses, are now available and investigations are underway to determine their safety and efficiency in preparation for clinical application for a variety of diseases. Several novel non-viral based therapies have also been developed recently to lower LDL-C serum levels in FH patients. This article reviews the progress made in the 18 years since the first clinical trial for gene therapy of FH, with emphasis on the development, design, performance and limitations of viral based gene transfer vectors used in studies to ameliorate the effects of LDLR deficiency.